HUMAN DIMENSION IN LOW INCOME SETTLEMENTS DEVELOPMENT - Johan Silas (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
The main reason of The Millennium Development Goals (MDGs) agreed in thegeneral session of the UN in 2000 was to respond to the alarming situation ofpoverty experienced by a large number of people all over the world, from developing countries to developed countries seen after the 2007-2008 financialcrisis that not yet over, and no effective solution has yet to be found for the US and EU. Japan is still struggling very hard to revive their slumbering economy with no solution in sight. In overcoming poverty problem, simple financial intervention such as special grant given to the poor by the Indonesian government was not a solution rather to appease people from political sentiment cause by economic and financial problem after a certain political decision was made, such as increasing the price of vehicle fuel. Poverty can effectively be resolve if the poor can be freed from their burden, especially if the burden was caused by inability of government to fulfill their responsibility and duty as given by the constitution and laws. Next as important is the fact that people were given a wide possibility to achieve their live time goals of what they wanted to be. As most part of a city consist of housing and human settlements, it is extremely important to put the human dimension as focus for housing and human settlements development. This paper will draw and learn the lessons from the vast experience in rebuilding housing and human settlements after the mega disaster in Aceh and Nias (late 2004) as well as what the city governmenthas done in lowering the number of its citizens categorized as the poor. If Vitruvius postulates that architecture consist or aimed mainly in the excellence of the dimension of beauty, strength and function, than it is also important to include the human aspect as the fourth dimension. Housing and human settlements development is not a self standing endeavor but it is part of a wider intervention needed to resolve the poverty issues of people that has to struggle to make ends meet for their family.